Graphene-assisted improve electrochemical performance of manganese vanadium oxide for aqueous zinc-ion battery - Xiaowen Niu; Jianhai Chen; Yongtao Tan (Next Energy, 2024)
Layer spacing of vanadium oxide can be effectively expanded by metal ion, however, its conductivity and electrochemical kinetics still require improvement. This work expands the layer spacing using manganese ion and help to improve conductivity and electrochemical kinetics by graphene. The results demonstrate that the layer spacing can be adjusted from 12.1 Å for pristine vanadium oxide (VOH) to 13.6 Å for manganese vanadium oxide (MnVO). Due to graphene introduction, it decreases to 11.6 Å for manganese vanadium oxide/graphene composite (MnVO-0.05–8/GN-15). Notably, the optimized composite delivers higher specific capacity of 507.5 mAh g−1 for MnVO-0.05–8/GN-15 than that of MnVO (410.4 mAh g−1) and VOH (370.1 mAh g−1) at current density of 0.5 A g−1. Furthermore, the MnVO-0.05–8/GN-15 exhibits fast Zn2+ ion diffusion ability, achieving high energy density of 403.51 Wh kg−1 and retaining an excellent cycle stability of 85.7% after 2000 cycles at a current density of 3 A g−1.